The Department of Philology, Universitatea Petrol-Gaze din Ploieşti - (:unkn) unknown (My University, 2026)
The Arts of Healing: Cultural Narratives of Trauma The Department of Philology, Universitatea Petrol-Gaze din Ploieşti, The Centre of Literary Studies, Linguistics, Theory of Criticism and Culture, Romania. 3-5 November 2016 “The Odyssey of Nikos Kouroussis: Loss, Trauma, Affect and the Material that Passes into Sensation.”